Mandibular Lytic Lesion in Familial Paraganglioma Syndrome Type I: A Clinical Conundrum. (August 2017) - Sinha, Parul; Yuen, Sonia N.; Chernock, Rebecca D.; Haughey, Bruce H.
Objective: The entity of primary mandibular paraganglioma (PGL) is not well accepted within the head and neck. Mandibular PGLs hitherto reported in literature are malignant metastatic lesions, mostly from a pheochromocytoma. Methods: We report a case of mandibular lytic lesion in a young female with multifocal PGLs but no family history of PGLs. We also performed a literature search to identify published cases of mandibular PGL. Results: Lack of established criteria for malignancy in a PGL made diagnosis and treatment challenging. Testing was negative for a pheochromocytoma and positive for mutation of succinate dehydrogenase gene encoding subunit D (SDHD), thus rendering a diagnosis of familial PGL syndrome type I. Due to the absence of prior published reports of nonmalignant, primary mandibular PGL, patient was treated with surgery and postoperative radiotherapy. Our literature search revealed 4 published cases of mandibular PGL, all of which had an osteoblastic appearance and were malignant. Conclusions: Isolated mandibular PGL does not always indicate a malignant metastatic lesion. Genetic testing is recommended in patients with early onset of PGL and/or multifocality even without a positive family history. Surgical resection alone with surveillance can be offered for such isolated lesions in the presence of familial PGL syndrome type I.